1993
DOI: 10.1093/ajcn/58.2.307s
|View full text |Cite
|
Sign up to set email alerts
|

Food demands of the emerging consumer: the role of modern food technology in meeting that challenge

Abstract: Traditionally, the food industry has not been driven by technology. However, over the past decade, enormous changes have been introduced because of the changing demographics and evolving lifestyle of the consumer; the public health policies driving these lifestyle alterations; the growing fitness food market, which is a consequence of these changes; and the new aggressive posture taken by the food industry toward use of innovative technologies to satisfy consumer needs. This review is a brief description of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The considerable burden of foodborne illness on Canadian society deserves the attention of governments at all levels, the food industry, and the consumers themselves, who, in the final analysis, are their own last line of defense against foodborne hazards. The process of ensuring the safety of the food supply needs to be dynamic and flexible, permitting it to adapt to constant change in the types of food consumed, the geographic origins of food products and the ways in which different foods are processed (41).…”
Section: Factors Responsible For the High Level Of Foodborne Illnessmentioning
confidence: 99%
“…The considerable burden of foodborne illness on Canadian society deserves the attention of governments at all levels, the food industry, and the consumers themselves, who, in the final analysis, are their own last line of defense against foodborne hazards. The process of ensuring the safety of the food supply needs to be dynamic and flexible, permitting it to adapt to constant change in the types of food consumed, the geographic origins of food products and the ways in which different foods are processed (41).…”
Section: Factors Responsible For the High Level Of Foodborne Illnessmentioning
confidence: 99%
“…In addition food processors have begun offering a variety of leaner, processed meats and lower-fat milks. Smith (1993) observed that, traditionally, the food industry has not been technology driven. Yet, four recent forces will move the food industry towards greater use of technology to create marketable products.…”
Section: Crop Improvements and Chronic Diseasementioning
confidence: 99%
“…Some of these objectives will be attained by altering the nutritional properties of existing food. This can be achieved through biotechnology (Hayenga, 1993), through new food and ingredient processing technologies (Smith, 1993) and through simple enrichment of foods. An important strategic decision in nutrition policy is to identify which goals might be achieved through an altered food supply and which goals might be achieved through the technological modification of existing food supplies.…”
Section: Options For the Attainment Of Nutrition Policy Objectivesmentioning
confidence: 99%